Eventos adversos em pacientes portadores de cateter venoso central - Jean Alves Bulcão (2018)
Introduction: The central venous catheters are important health devices for the maintenance of venous therapies in health care, especially in high complexity units and in intensive care patients who need surveillance. The insertion of CVC is of medical competence, for its indication one must take into account the possible risks and complications involved with the use of the therapy. Adverse events related to the use of central venous catheters are studying due to invasive technique, which can cause harm and if poorly used for those submitted to the procedure. Thus, rigid protocols to indicate the rules of asepsis and antisepsis, as well as catheter maintenance, are crucial to minimize the likelihood of complications. Central venous catheter complications can be local and systemic among them are infiltration, extravasation, phlebitis, obstruction, thrombosis, infection, hyperthermia, embolism, pneumothorax, hemothorax and even death. Objective: The objective is analyze the adverse events in patients with Central Venous Catheter. Method: This study is a retrospective document, with a quantitative method of data analysis. The information was collet in the Federal Public Hospital placed on Belo Horizonte, in the period of June and July of 2017 by the researcher, using secondary data from the records book of the surgical procedures of the Surgical Center. In this moment, the researcher sought all patients who underwent central venous catheterization from September 2016 to November 2016 and from their respective medical records. The sample consisted of 60 patient files. Results: The results were described with the sociodemographic and clinical characterization of the patients, adverse events related to the patient and the CVC, factors that influence the occurrence of urgency in the implantation of CVC and factors that influence the occurrence of hyperthermia. As results obtained: Male subjects are 36 (60.00%), with a mean age of 23.04 years, with a standard deviation of 25.46, most patients 50 (83.33%), (40.00%), the groups with the highest frequencies were ASA II and ASA III with 23 (39.66%), the type of catheter most used was the Hemodialysis / Permicath Catheter with 22 (36.67%). When we analyzed the time of permanence of the catheter 30 (50.00%) presented a time between 1 and 10 days. Twenty-seven patients (45.00%) had a jugular vein at the site of insertion, and 46 (76.67%) of the type of precaution presented by the subjects was the standard precaution. Of the complications analyzed, the most prevalent were catheter infection and occlusion with 3 (5.00%), and the most frequent signs at catheter insertion present bleeding with 11 (18.33%). But the largest number of patients (81.67%), the vast majority of the patients did not present hypertemia 42 (70.00%) and the most frequent comorbidity was renal or urinary tract disease with 28 (46.67%). Conclusion: The events found evidenced a great relation with the techniques used in the insertion, the care, in the way of using the catheters and maintenance of the catheters. Thus, it is necessary to create a monitoring team of the adverse effects that uses through the application of quality indicators with the purpose of benefiting in the improvement of the safety and assistance provided to the patient. For this, it is necessary that the professional takes a critical look at the patient's problems to work in search of solutions that provide improvements in clinical practice and that strengthen patient safety.